Adult-onset vanishing white matter disease caused by the EIF2B5 c.185A>T (p.Asp62Val) variant - Zhou, Jie; Ji, Chunbo; Ma, Siqing; Zhu, Jianying; Yang, Ping (Frontiers in Genetics, 2026)
BackgroundVanishing white matter disease (VWMD; OMIM 603896), also known as childhood ataxia with central nervous system hypomyelination (CACH), is a rare autosomal recessive leukodystrophy caused by pathogenic variants in the EIF2B gene family (EIF2B1–EIF2B5). Clinical manifestations are highly heterogeneous, with onset ranging from fetal life to adulthood; adult-onset cases remain relatively rare and often present with atypical symptoms. Brain magnetic resonance imaging (MRI) and genetic testing are pivotal for diagnosis.Case PresentationWe report a 32-year-old Chinese female with adult-onset VWMD characterized by intermittent headaches, progressive cognitive decline, menstrual irregularities, and hearing loss. Cranial MRI with diffusion-weighted imaging (DWI) revealed symmetrical periventricular and centrum semiovale white matter abnormalities. Whole-exome sequencing (WES) identified a homozygous missense variant in the EIF2B5 gene, formatted per Human Genome Variation Society (HGVS) guidelines as NM_001414.4:c.185A>T (p.Asp62Val). This variant was previously documented exclusively in a pediatric patient, representing the first report in an adult.ConclusionOur case expands the phenotypic and age-related spectrum of EIF2B5-associated VWMD, highlighting that the c.185A>T variant is capable of manifesting in adulthood with non-classical features (e.g., headache as the initial symptom). Prior studies have confirmed that this variant impairs EIF2B complex function, which reinforces its pathogenic role in disrupting the integrated stress response (ISR) and maintaining white matter homeostasis. A literature review of 99 genetically confirmed adult-onset VWMD cases further underscores genotype–phenotype correlations: EIF2B5 is the most frequently mutated subunit in adult patients, with cerebellar ataxia, cognitive decline, and psychiatric symptoms as the predominant initial manifestations. Female patients often present with premature ovarian failure, a key diagnostic hallmark. Early genetic testing is crucial for definitive diagnosis, prenatal counseling, and symptomatic management. Notably, this study has limitations, including the lack of investigation into gene-gene interactions—factors that may modulate disease severity and phenotypic variability—and the unavailability of parental genetic data to fully validate zygosity.